2006
DOI: 10.1038/sj.ki.5000020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of manipulating serum phosphorus with phosphate binder on circulating PTH and FGF23 in renal failure rats

Abstract: Phosphorus directly controls parathyroid hormone (PTH) synthesis and secretion. Serum levels of the novel phosphate-regulating hormone, fibroblast growth factor 23 (FGF23), are positively correlated with hyperphosphatemia in patients with chronic renal insufficiency (CRI). We proposed that changes in serum PTH and FGF23 levels might be associated with changes in serum phosphorus levels caused by the phosphate binder sevelamer hydrochloride (sevelamer, i.e. crosslinked poly[allylamine hydrochloride]). Rats were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
126
3
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 131 publications
(145 citation statements)
references
References 26 publications
15
126
3
1
Order By: Relevance
“…increased serum phosphate and FGF23) could be induced in mice with a 4 mg adenine/day gavage without substantial effects on bodyweight loss, and mortality. The increase in serum phosphate in mice receiving an adenine gavage was similar to what has been reported in studies using rats [8]. Increases in kidney weight and serum urea were consistent with renal dysfunction [11,14].…”
Section: Discussionsupporting
confidence: 74%
See 4 more Smart Citations
“…increased serum phosphate and FGF23) could be induced in mice with a 4 mg adenine/day gavage without substantial effects on bodyweight loss, and mortality. The increase in serum phosphate in mice receiving an adenine gavage was similar to what has been reported in studies using rats [8]. Increases in kidney weight and serum urea were consistent with renal dysfunction [11,14].…”
Section: Discussionsupporting
confidence: 74%
“…During the gavage studies, it was noted that the stomachs were enlarged in mice treated with adenine. While it had been previously reported that CKD could alter gastrointestinal motility [33], there was no mention in the animal literature of enlarged stomachs [8,13,14]. The significant enlargement of the stomach caused by adenine supplementation suggested that adenine use in the mouse model might compromise oral administration of test therapies.…”
Section: Discussionmentioning
confidence: 74%
See 3 more Smart Citations